Peran Hadis Dalam Pembaruan Hukum Islam Masa Kini (As-Sahla: Journal Of Islamic Studies, 2025)
The study of hadith in the contemporary era faces significant challenges regarding the relevance of Islamic law to modern dynamics. This research aims to examine the role of hadith in the reform of Islamic law today using a qualitative library research approach. Data were collected from primary hadith compilations, ushul fiqh literature, classical and contemporary scholars’ works, and journal articles published in the last decade. The data were analyzed using content analysis combined with the maqāṣid al-sharī‘ah and contextual-historical approaches. The findings reveal that hadith continues to play a strategic role as the second source of Islamic law after the Qur’an. Hadith functions not only as a normative text but also as an adaptive source of ijtihad in addressing modern issues such as digitalized worship, Islamic financial technology, medical bioethics, and multicultural family law. The novelty of this study lies in its integrative analysis that combines the authority of hadith with maqāṣid al-sharī‘ah principles, resulting in a paradigm of Islamic legal reform that is more applicable, just, and relevant to global needs. This study is expected to enrich contemporary hadith literature and provide practical contributions for scholars, academics, and policymakers in developing Islamic law that is responsive to the demands of modernity.